2019
DOI: 10.1038/s42003-019-0354-1
|View full text |Cite
|
Sign up to set email alerts
|

Tasselseed5 overexpresses a wound-inducible enzyme, ZmCYP94B1, that affects jasmonate catabolism, sex determination, and plant architecture in maize

Abstract: Maize is monecious, with separate male and female inflorescences. Maize flowers are initially bisexual but achieve separate sexual identities through organ arrest. Loss-of-function mutants in the jasmonic acid (JA) pathway have only female flowers due to failure to abort silks in the tassel. Tasselseed5 (Ts5) shares this phenotype but is dominant. Positional cloning and transcriptomics of tassels identified an ectopically expressed gene in the CYP94B subfamily, Ts5 (ZmCYP94B1). CYP94B enzymes are wound inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 74 publications
1
48
0
Order By: Relevance
“…These observations suggest that the elevated expression of GRMZM2G177668 (Chau et al ; Chattopadhyay et al ) in the Ts5 mutant leads to lower JA‐Ile contents and feminization of the tassels. A recent study also mapped Ts5 mutant using positional cloning and transcriptomics; they showed that Ts5 mutant phenotype is caused by the ectopic expression of ZmCYP94B1 (GRMZM2G177668) (Lunde et al ). Two independent groups cloned Ts5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that the elevated expression of GRMZM2G177668 (Chau et al ; Chattopadhyay et al ) in the Ts5 mutant leads to lower JA‐Ile contents and feminization of the tassels. A recent study also mapped Ts5 mutant using positional cloning and transcriptomics; they showed that Ts5 mutant phenotype is caused by the ectopic expression of ZmCYP94B1 (GRMZM2G177668) (Lunde et al ). Two independent groups cloned Ts5 .…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of AtCYP94B1 or AtCYP94B3 in Arabidopsis leads to a partial loss of fertility (Koo et al ). A recent study demonstrated that the Ts5 mutant phenotype is caused by the ectopic expression of ZmCYP94B1 (GRMZM2G177668), as revealed using positional cloning and transcriptomics (Lunde et al ). Here, we also demonstrated that the overexpression of GRMZM2G177668 leads to the tassel‐seed phenotype in transgenic maize plants (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…JA is integral to environmental responsiveness and developmental progression; regulators of JA, JA biosynthetic genes, and JA signaling proteins influence pest/pathogen sensitivity(38, 39), wound response(22, 40, 41), cell expansion(33), and sex determination and floral organ progression (specifically, anther and pistil development)(7, 1517, 22, 27, 42, 43). Barley, rice, and maize display complex mechanisms of floral development.…”
Section: Discussionmentioning
confidence: 99%
“…MSD1 is expressed in a narrow spatiotemporal window within the developing panicle in wild type (WT), BTx623; its expression is dramatically reduced in EMS-induced msd1 mutants. Many genes involved in JA biosynthesis, including 12-oxophytodeinoate reductase 3 ( OPR3 )(18, 19), allene oxide synthase ( AOS )(20), cytochrome P450(21, 22), and lipoxygenase ( LOX )(23), are also downregulated in msd1 mutants. MSD1 is thought to activate the programmed cell death pathway through activation of JA biosynthesis, which destines the PS to abortion.…”
Section: Introductionmentioning
confidence: 99%
“… Scheme on pathways in TASSELSEED1(TS1)‐, TS2‐, and TS5‐mediated formation and metabolism of jasmonic acid compounds leading to altered gene expression and pistil elimination in maize In plastids (P), linolenic acid (18:3) is converted by the TS1 encoded 13‐lipoxygenase (LOX), by an allene oxide synthase (AOS) and by an allene oxide cylase (AOC) to 12‐oxo‐phytodienoic acid (OPDA), and is transported to peroxisomes (perox), where it is reduced by an OPDA reductase1(OPR1) and is shortened in the carboxylic acid side chain by the ß‐oxidation machinery including a short chain dehydrogenase (TS2) to JA occurring in the cytosol. A JA glucoside is formed by the UDP‐glycosyl transferase (SILKLESS1, SK1), whereas JA‐Ile is formed by a synthetase (JAR1) and can be hydroxylated by the CYP94B1 enzyme (=TS5) (Lunde et al 2019; Wang et al 2020). Finally, JA‐Ile‐induced gene expression leads to pistil elimination which is diminished by SK1 and TS5 activity due to their decrease in the amount of active JA/JA‐Ile.…”
mentioning
confidence: 99%